Torsional injuries of the lower limb: an analysis of the frictional torque between different types of football turf and the shoe outsole - Smeets, K.; Jacobs, P.; Hertogs, R.; Luyckx, J.-P.; Innocenti, B.; Corten, K.; Ekstrand, J.; Bellemans, J. (British Journal of Sports Medicine, 2012)
Background Football turf is increasingly used in European soccer competition. Little is known on the rotational torque that players experience on these fields. High rotational torques between the shoe outsole and the sports surface has been correlated with torsional injuries of the lower limb and knee. Purpose To evaluate the effect of six parameters that could influence the rotational torque between the shoe outsole and the latest generation football turf. Study design Controlled laboratory study. Methods A testing apparatus was constructed to measure the peak torque generated during a controlled rotation of the foot. Six parameters that could potentially influence the frictional forces, were considered: (1) the sports surface, (2) the shoe outsole cleat design, (3) the weather conditions, (4) the weight, (5) the presence of an impact and (6) the direction of rotation. Results The football turf without infill showed significantly lower frictional torques than natural grass whereas a football turf with sand/rubber infill had significantly higher torques. Blades were associated with significantly higher torques than studs on natural grass and on one football turf with sand/rubber infill. Dry weather was associated with higher torques only for the football turf without infill. The torque increased linearly and significantly with an increasing vertical load. The rotational torque increased significantly following an impact. Torques on external rotational movements were significantly higher with blades. Conclusions Important differences in rotational torques are found and could be seen as potential risk factors for torsional injuries of the lower limb.